Understanding Determinants of Domestic Tourism Intentions During The Covid-19 Pandemic in Indonesia - Ketut Wahyu Kusumadewa Penatih; Khoirunurrofik Khoirunurrofik (Green Publisher Indonesia, 2025)
This research is based on Azjen's theory of Planned Behavior (TPB) and analyzes travel intention as the dependent variable and then pandemic fatigue, health risks, media communication and government policies as independent variables. Data collection was carried out online with a total of 206 respondents (N-206) and then analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) approach and conducted interviews to deepen the results. The results of data analysis show that the factors that influence travel intentions are Pandemic Fatigue, Media Communication and Government Policy, while health risks do not affect travel intentions. Thus, the government can implement health control policies to reduce severity, such as vaccination and implementation of health protocols, improving the quality of service in tourist areas as well as increasing tourism branding and promotion in increasing travel intentions.